NATURE AND TYPE OF COLLABORATIVE RESEARCH AS REFLECTED IN SELECTED THEORETICAL POPULATION GENETICS LITERATURE - Gupta, B.M.; Karisiddippa, C.R. (Malaysian Journal of Library and Information Science, 1998)
Indicates the nature and types of collaborated research as reflected in selected theoretical population genetics literature from 1956 - 80, and studies the role of funding. Highlights the research priorities of few important countries in collaborative research, and the collaboration linkages among various countries in transnational collaborative research. Concludes that with time, the focus of research is slowly shifting from internal collaboration to domestic and international collaboration, supported by increasing funding from government agencies in theoretical population genetics research.